Mechanisms associated with tiller suppression under stagnant flooding in rice - Zhu, Guanglong; Chen, Yutiao; Ella, Evangelina S.; Ismail, Abdelbagi M. (Wiley, 2019)
Stagnant flooding (SF) during vegetative growth triggers stem elongation usually at the cost of tiller production in rice, reducing grain yield. To explore physiological mechanisms associated with tillering suppression under SF, three contrasting genotypes (Swarna and Swarna‐Sub1, both sensitive and IRRI154, tolerant) were evaluated under standing water depths of 0, 5, 30 and 50 cm. SF significantly suppressed tiller formation but increased plant height, root biomass, shoot elongation (ratio of plant height before and after flooding), leaf emergency and non‐structural carbohydrate (NSC) concentration (in root–shoot junction) in all genotypes at the early stage of development. Chlorophyll concentration in the upper leaves (upper most fully expanded leaf at top) was higher than in lower leaves (lowest green leaf at base), but decreased under SF in both. SF increased hydrogen peroxide (H2O2) at the early stage of treatment, with concomitant increase in malondialdehyde (MDA) production by stems and leaves. MDA concentration in root–shoot junction increased but delayed. Tiller number correlated negatively with plant height, shoot elongation, leaf emergency, MDA concentration in leaves and root–shoot junction, root biomass, and NSC concentration in the root–shoot junction. The results suggested existence of compensatory mechanisms between tiller growth and shoot elongation in rice for resilience under SF, where energy is mainly diverted for shoot elongation to escape flooding. The SF‐tolerant genotype produced less H2O2 and maintained energy balance for higher survival and better growth under stagnant flooding.